Pattern of calcification on CT and FDG-PET of a rare perineural mantle cell lymphoma: a potential of non-histological imaging marker - Ahmad Saad, Fathinul Fikri; Shakher, Ramdave; Nordin, Abdul Jalil (Universiti Putra Malaysia Press, 2016)
The presence of calcification in a particular FDG-avid soft tissue lesion may at times present uncertainty regarding the clinical course of the disease pathology. Calcific deposits are not specific for either benign or malignant aetiologies (Brant et al., 2010). Altered glucose metabolism with associated calcification may underpin underlying aggressive pathophysiology with necrosis as sequelae. Mantle Cell Lymphoma (MCL) is a subtype of non-Hodgkin’s lymphoma. It is a rare B-cell NHL that is prevalent in men over the age of 60. The disease may be aggressive but it can also behave in a more indolent fashion in some patients. MCL comprises about 5% of all NHLs. The disease is called Mantle Cell Lymphoma because the tumour cells originally come from the ‘mantle zone’ of the lymph node (Zhou et al., 2004). Pretreatment Hodgkin’s lymphoma with calcification may masquerade as other second primary pathologies, e.g. extraosseous osteosarcoma or myositis ossificans (Apter et al., 2002; Korek-Amorosa et al., 1974). A calcified perineural lymphoma prior to treatment is exceedingly rare and calcification usually occurs one to five years after chemotherapy or radiation therapy with an incidence of 2% (Apter et al., 2002). This case documents how the manifestation of a rare malignant perineural mantle cell lymphoma may be indistinguishable from other pathological entities based on its pattern of distribution in a combined FDG-PET-CT study.